Antituberculosis, drug-fraction interaction and cytotoxicity activities of tetracera macrophylla stem extract - Mazlun, Muhamad Harith (2021)
Tetracera macrophylla is a climbing woody vine that has been used by several ethnics of indigenous people around Malaysia for various ethnomedicinal purposes. With the emergence of resistance strains of Mycobacterium tuberculosis, T. macrophylla could be a potential reservoir in quest of novel anti-TB compounds. This research hence embarks on achieving three objectives which are to assess the anti-TB activities of T. macrophylla stem fractions against M. tuberculosis H37Ra, to evaluate the synergistic interactions of T. macrophylla stem fractions with anti-TB drugs (Rifampicin and Isoniazid) and to assess cytotoxicity of stem fractions of T. macrophylla to Human Embryonic Kidney (HEK-293) cell line. Fractionation via column and thin-layer chromatography of the plant ethyl acetate extract has led to the elution of 29 fractions. Anti-TB activities assessment of all T. macrophylla fractions via Tetrazolum Microplate Assay (TEMA) has revealed that seven of the fractions (S2, S3, S5, S6, S11, S12 & S15) inhibited the growth of mycobacteria at Minimum Inhibition Concentration (MIC) ranges from 400 to 800 µg/ml though with Minimum Bactericidal Concentration (MBC) that were more than 800 µg/ml. Furthermore, the evaluation of synergistic interactions of selected bioactive fractions (S5, S6 & S12) with selected anti-TB drugs (Rifampicin and Isoniazid) via checkerboard assay has showed that the fractions exhibited additive effects with Fractional Inhibition Concentration Index (FICI) ranges from 0.625 to 1.125, suggesting that the fractions may possess a mechanism-of-action and drug target which resemble that of the anti-TB drugs. On the other hand, the selectivity index (SI) as calculated from the cytotoxicity assay via tetrazolium colorimetric-based method has displayed that all of the test fractions were more selective towards the mammalian cells than the mycobacterial cells. Conclusively, present study has provided insight into anti-TB potential of T. macrophylla and further scientifically consolidate the species as an anti-TB ethnomedicinal importance.